Effect of 30 days of ketogenic Mediterranean diet with phytoextracts on athletes' gut microbiome composition - Mancin, Laura; Amatori, Stefano; Caprio, Massimiliano; Sattin, Eleonora; Bertoldi, Loris; Cenci, Lorenzo; Sisti, Davide; Bianco, Antonino; Paoli, Antonio (Frontiers in Nutrition, 2022)
Background Recent research suggest that gut microbiome may play a fundamental role in athlete's health and performance. Interestingly, nutrition can affect athletic performance by influencing the gut microbiome composition. Among different dietary patterns, ketogenic diet represents an efficient nutritional approach to get adequate body composition in athletes, however, some concerns have been raised about its potential detrimental effect on gut microbiome. To the best of our knowledge, only one study investigated the effect of ketogenic diet on the gut microbiome in athletes (elite race walkers), whilst no studies are available in a model of mixed endurance/power sport such as soccer. This study aimed to investigate the influence of a ketogenic Mediterranean diet with phytoextracts (KEMEPHY) diet on gut microbiome composition in a cohort of semi-professional soccer players. Methods 16 male soccer players were randomly assigned to KEMEPHY diet (KDP n = 8) or western diet (WD n = 8). Body composition, performance measurements and gut microbiome composition were measured before and after 30 days of intervention by 16S rRNA amplicon sequencing. Alpha-diversity measures and PERMANOVA was used to investigate pre-post differences in the relative abundance of all taxonomic levels (from phylum to genus) and Spearman's correlations was used to investigate associations between microbial composition and macronutrient intake. Linear discriminant analysis was also performed at the different taxonomic levels on the post-intervention data. Results No differences were found between pre and post- dietary intervention for microbial community diversity: no significant effects of time (p = 0.056, ES = 0.486 and p = 0.129, ES = 0.388, respectively for OTUs number and Shannon's ENS), group (p = 0.317, ES = 0.180 and p = 0.809, ES = 0.047) or time × group (p = 0.999, ES = 0.01 and p = 0.230, ES = 0.315). Post-hoc paired Wilcoxon test showed a significant time × group effect for Actinobacteriota (p = 0.021, ES = 0.578), which increased in the WD group (median pre: 1.7%; median post: 2.3%) and decreased in the KEMEPHY group (median pre: 4.3%; median post: 1.7%). At genus level, the linear discriminant analysis in the post intervention differentiated the two groups for Bifidobacterium genus (pertaining to the Actinobacteria phylum), Butyricicoccus and Acidaminococcus genera, all more abundant in the WD group, and for Clostridia UCG-014 (order, family, and genus), Butyricimonas, Odoribacterter genera (pertaining to the Marinifilaceae family), and Ruminococcus genus, all more abundant in the KEMEPHY group. Conclusions Our results demonstrate that 30 days of KEMEPHY intervention, in contrast with previous research on ketogenic diet and gut microbiome, do not modify the overall composition of gut microbiome in a cohort of athletes. KEMEPHY dietary pattern may represent an alternative and safety tool for maintaining and/or regulating the composition of gut microbiome in athletes practicing regular exercise. Due to the fact that not all ketogenic diets are equal, we hypothesized that each version of ketogenic diet, with different kind of nutrients or macronutrients partitioning, may differently affect the human gut microbiome.